1992
DOI: 10.1172/jci115735
|View full text |Cite
|
Sign up to set email alerts
|

Crosstransplantation of kidneys in normal and Hyp mice. Evidence that the Hyp mouse phenotype is unrelated to an intrinsic renal defect.

Abstract: Although deranged phosphate transport is the fundamental abnormality in X-linked hypophosphatemic (XLH) rickets, it remains unknown if this defect is the consequence of an intrinsic kidney abnormality or aberrant production of a humoral factor. To discriminate between these possibilities, we examined phosphate homeostasis in normal and Hyp mice, subjected to renal crosstransplantation. We initially evaluated the effects of uninephrectomy on the indices of phosphate metabolism that identify the mutant biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(89 citation statements)
references
References 33 publications
9
78
0
2
Order By: Relevance
“…Similar biochemical findings to TIO also are observed in X-linked hypophosphatemic rickets͞ osteomalacia (XLH), its murine homologue, Hyp, and autosomal dominant hypophosphatemic rickets (ADHR) (7). In addition, several lines of evidence indicate that XLH and Hyp are caused by a humoral mechanism (7)(8)(9)(10). Therefore, it is possible that TIO and XLH derive from a common or at least very similar humoral factor(s).…”
mentioning
confidence: 62%
“…Similar biochemical findings to TIO also are observed in X-linked hypophosphatemic rickets͞ osteomalacia (XLH), its murine homologue, Hyp, and autosomal dominant hypophosphatemic rickets (ADHR) (7). In addition, several lines of evidence indicate that XLH and Hyp are caused by a humoral mechanism (7)(8)(9)(10). Therefore, it is possible that TIO and XLH derive from a common or at least very similar humoral factor(s).…”
mentioning
confidence: 62%
“…(44) Thus, it has been proposed that the accumulation of a secreted, circulating substrate of PHEX, present in the absence of this enzyme, contributes to the XLH/Hyp phenotype. (81)(82)(83)(84)(85)(86) In addition to this systemic, phosphaturic change initiated by the loss of PHEX activity, it is also reasonable to consider that more local, direct changes in the extracellular matrix of bone might occur that could affect mineralization. Indeed, previous in vivo studies have shown partial correction of the osteomalacic phenotype when Phex/PHEX is overexpressed in osteoblasts, (83,84) and local, microenvironmental effects of PHEX within the extracellular matrix have been explicitly proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Serum 1,25-dihydroxy vitamin-D 3 levels were estimated using the method of Reinhardt et al [66]. Analysis of data for fractional excretion of phosphate (FEP) was carried out following the same method described previously by Shimada et al [82] for FGF23 bolus administration studies and by Nesbitt et al [57] for renal cross-transplantation experiments in Hyp mice.…”
Section: Serum and Urine Assaysmentioning
confidence: 99%
“…However, extensive studies in Hyp mice indicate that the defect in mineralization and renal function is mediated by circulating factor(s) derived from Phex defective osteoblasts. These investigations include parabiosis experiments [48,49], Hyp/normal kidney cross-transplantations [57], Hyp/normal osteoblast intra-muscular cross-transplantation and mineralization studies [18,[20][21][22]102], Hyp osteoblast conditioned media phosphate-uptake and mineralization studies [58,59,101], PHEX antisense studies in normal osteoblasts [80], demonstration of intrinsic abnormalities in the Hyp osteoblast [13,30,50,67,69] and direct analysis of mineralization inhibition and phosphate-uptake inhibition activity of Hyp serum [37]. Thus, in Hyp, the evidence strongly implicates a circulating humoral factor or factors [phosphatonin(s)] that are secreted by the Hyp osteoblast and impact on mineralization and renal phosphate handling.…”
Section: Introductionmentioning
confidence: 99%